PROGRAM UNGGULAN SMA NEGERI 2 RAMBAH HILIR SEBAGAI IMPLEMENTASI KEBIJAKAN PROGRAM ADIWIYATA DALAM PENCAPAIAN VISI SEKOLAH - Pariang Sonang Siregar; Hasrijal Hasrijal (JURNAL PENDIDIKAN ROKANIA, 2016)
This qualitative research aims to obtain an understanding of the implementation process of Adiwiyata in order to achieve the school vision of SMAN 2 Rambah Hilir Rokan Hulu, Riau Province. The results found that the implementation of the Adiwiyata program policy at SMAN 2 Rambah Hilir could be understood well by school community, the school is successful conducted based on the principles Adiwiyata program: educational, participatory, sustainable, and green school physically and beautiful. However, that are some limited obstacles facing by the school. By implementing this Adiwiyata policy, much effects has occurred: behavior changing of students (environmental awareness) of Adiwiyata program.